2021
DOI: 10.47391/jpma.1696
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged lockdown: psychological risk factors among children and their mental health

Abstract: The most talked phenomenon and sui generis of the modern time, the coronavirus diseases-2019 impacted individuals in a variety of ways. Older adults had a higher risk of vulnerability, while there were negative ramifications among children due to indirect impact. The preventive measures, including closing down of schools, malls and playgrounds as well as practising social distancing served as a shield against the hazard of outbreak. On the contrary, these strategies inculcated fear, anxiety, ambiguous communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Although the clinical symptoms of children infected with COVID-19 are milder than those of adults, and mortality is rare, studies showed that parents and children are especially vulnerable to feelings of emotional distress such as anger, depression, and irritability [ 2 ]. Many factors exacerbate their mental wellbeing, including quarantine, infection fear, frustration, and financial loss [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Many studies reported that teenagers were particularly affected, as quarantine caused a sudden interruption of all their social activities [ 6 , 7 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinical symptoms of children infected with COVID-19 are milder than those of adults, and mortality is rare, studies showed that parents and children are especially vulnerable to feelings of emotional distress such as anger, depression, and irritability [ 2 ]. Many factors exacerbate their mental wellbeing, including quarantine, infection fear, frustration, and financial loss [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. Many studies reported that teenagers were particularly affected, as quarantine caused a sudden interruption of all their social activities [ 6 , 7 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the COVID-19 pandemic, parents also showed increasing symptoms of anxiety, fatigue, sleeping disorders, and depression [ 2 , 10 ]. Reports also indicated that parents experiencing social isolation, unemployment, and financial instability showed increased signs of child neglect and maltreatment [ 8 , 9 ]. Parents of hospitalized children during the pandemic showed higher symptoms of stress and anxiety than those of parents of children who were not hospitalized [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%